IMPLEMENTATION OF SCHOOL TV DIGITAL LIBRARY TO DEVELOP LINGUISTIC LITERACY INTELLIGENCE IN EARLY CHILDREN - kasiati sulaiman; Sri Watini; Santy Hataul; Hikmah Pertiwi; Masita Nunlehu; Cahyani Setiawati (International Conferences on Early Childhood Education Proceedings, 2023)
The purpose of this research is to describe the introduction of digital school television libraries as a strategy for developing language skills in early childhood. This study used a qualitative approach involving children aged 5-6 years who participated. Data collection methods include observation, interviews, and document analysis. The results of the study suggest that the introduction of digital school television libraries may have a positive impact on the development of early childhood language skills. Participants indicated that their speaking, reading and writing skills improved as they explored the variety of content offered in the digital TV library. In addition, participants also showed increased interest and motivation in reading and writing activities. This study will help us better understand the benefits of digital TV libraries in developing early childhood language skills.